The determinant of bankruptcy : a case of Malaysia / Nursyafiqah Abdul Rahim - Abdul Rahim, Nursyafiqah (Universiti Teknologi Mara Perlis, 2020)
Bankruptcy is one of the serious issues in Malaysia and the determinants of bankruptcy is rarely been explored. The statistic in Department of Insolvency recorded the increasing number of bankruptcies especially in Malaysia. In this research paper, the determinant of bankruptcy in Malaysia was evaluated. The main objective of this research paper is to increase the awareness among individual on the factors that lead to bankruptcy. Therefore, the individual can take a corrective action to avoid themselves from bankrupt. There are three determinants included in this research paper which are unemployment, lending rate, credit card and non-performing loan. The E-views is used as a tool for analyzing the study on the relationship between unemployment, lending rate, credit card and non-performing loan toward bankruptcy.